Paediatric Cogan´s syndrome - review of literature, case report and practical approach to diagnosis and management - Kristina Rücklová; Thekla von Kalle; Assen Koitschev; Katrin Gekeler; Miriam Scheltdorf; Anita Heinkele; Friederike Blankenburg; Ina Kötter; Anton Hospach (Pediatric Rheumatology Online Journal, 2023)
Abstract Background Cogan´s syndrome is a rare, presumed autoimmune vasculitis of various vessels characterized by interstitial keratitis and vestibular impairment accompanied by sensorineural hearing loss. Due to the rarity of Cogan´s syndrome in children, therapeutic decision making may be challenging. Therefore, a literature search was performed to collect all published paediatric Cogan´s syndrome cases with their clinical characteristics, disease course, treatment modalities used and their outcome. The cohort was supplemented with our own patient. Main text Altogether, 55 paediatric Cogan´s syndrome patients aged median 12 years have been reported so far. These were identified in PubMed with the keywords “Cogan´s syndrome” and “children” or “childhood”. All patients suffered from inflammatory ocular and vestibulo-auditory symptoms. In addition, 32/55 (58%) manifested systemic symptoms with musculoskeletal involvement being the most common with a prevalence of 45%, followed by neurological and skin manifestations. Aortitis was detected in 9/55 (16%). Regarding prognosis, remission in ocular symptoms was attained in 69%, whereas only 32% achieved a significant improvement in auditory function. Mortality was 2/55. Our patient was an 8 year old girl who presented with bilateral uveitis and a history of long standing hearing deficit. She also complained of intermittent vertigo, subfebrile temperatures, abdominal pain with diarrhoea, fatigue and recurrent epistaxis. The diagnosis was supported by bilateral labyrinthitis seen on contrast-enhanced magnetic resonance imaging. Treatment with topical and systemic steroids was started immediately. As the effect on auditory function was only transient, infliximab was added early in the disease course. This led to a remission of ocular and systemic symptoms and a normalization of hearing in the right ear. Her left ear remained deaf and the girl is currently evaluated for a unilateral cochlear implantation. Conclusions This study presents an analysis of the largest cohort of paediatric Cogan´s syndrome patients. Based on the collected data, the first practical guide to a diagnostic work-up and treatment in children with Cogan´s syndrome is provided.